Towards ecological everything – The ecological university, ecological subjectivity and the ecological curriculum - Stratford, Robert J (Policy futures in education, 2024)
There are no perfect solutions to the complex mess the planet is in right now, but there might be some better directions for the contemporary ‘university in ruins’ (Readings, 1996). In a world of struggling liberal democracies, climate change, biodiversity loss and global pandemics, this paper builds on the philosophical work informing the Ecological University (Barnett, 2018; Stratford, 2019) to shore up the theoretical groundwork for an ecological approach to higher education. While such a concept is fanciful (or utopian) in many respects, the possibilities for an ‘ecological’ turn in higher education policy and practice – beyond liberal and neoliberal approaches to higher education – point towards university policy and practice requiring a clearer understanding of ecological subjectivity as a basis for an ecological curriculum in higher education. This paper explores how ecological subjectivity could be developed via the concept of Anthropocene Intelligence. It explores how Anthropocene Intelligence can be used as a way of challenging the mainstream, liberal context of the higher education curriculum. Several ways in which this might occur are pointed to with potential changes to economics teaching being detailed as an example of the transformation that might be possible in an ecological higher education curriculum.